Communications Strategy: Proposed Strategy for Phase II of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Proposed communications strategy for CCAFS Phase II, submitted to CGIAR Consortium 31 March 2016. Strategic communications offers a set of powerful tools and approaches that can contribute to CCAFS outcomes and CGIAR’s SRF, and generate positive change. The CCAFS communications strategy for Phase II builds on more than five years of successful communications in Phase I. In Phase II, communications activities continue to strongly align with the program’s impact pathways, and employ a suite of well-established tools and approaches to deliver tailored messages to program partners and next users. A systematic effort to monitor and evaluate communications activities will continue, to ensure that Phase II communications benefits from previous successes and lessons learned, and continues to learn and adjust as the program evolves.